Foreign Investment in Rapidly Growing Countries : - Kehal, H. S. (Palgrave MacMillan, 2005)
China and India have both received a great amount of focus from the foreign investors. However, there are acute differences in the implementation of the economic reforms; China made rapid progress in the manufacture of high technology products, whilst India progressed in the development of high technology. This book explores the contrasts between China and India in attracting, utilizing and related issues and discusses the challenges faced by the foreign investors.